Inovasi Pemanfaatan Teknologi Hidroponik dalam Ruangan Rumah Tidak Terpakai sebagai Upaya Pemenuhan Gizi Keluarga - Fastabiqul Khairad; Agung Jabar Nur (Universitas Medan Area, 2022)
Technological developments in agriculture are currently very fast with the creation of new innovations that can increase the productivity and quality of agricultural products, one of which is the hydroponic cultivation technique. Hydroponics is a method of growing plants without soil. Vertical hydroponics can optimize production even though the land is narrow. This research examines unused indoor verticulture hydroponic cultivation. Plants consist of mustard greens, pakcoy, lettuce, red spinach and green spinach. By utilizing a 9 m2 room, vertical hydroponic cultivation can be carried out using existing technology. Hydroponic cultivation in a vertical manner can fulfill the nutrition of a family of 2 adults and 1 teenager with the recommendations conveyed by WHO, namely 300-400 grams for adolescents and 400-600 grams for adults. In addition, with limited land, they are able to do farming which can increase income and meet the nutritional needs of the family. This indoor cultivation is better than conventional cultivation with an additional net income of Rp. 244,125 for one month from verticulture hydroponic cultivation by utilizing unused space.